1998
DOI: 10.1002/aic.690440107
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the quality of fluidization using the short‐term predictability of pressure fluctuations

Abstract: In uarious industrial applications of bubbling fluidized beds, defluidizing parts of the Fluidization QualityGas-solid fluidized beds are among the most important reactor systems in the chemical industry, because they offer excellent possibilities for dealing with chemical reactants in reaction systems in which good fluid mixing, high heat and mass-transfer rates, and low pressure drops are required. Typical examples of industrial applications of gas-solid fluidized beds include synthesis and catalytic reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 20 publications
(16 reference statements)
1
67
0
Order By: Relevance
“…hydrodynamics. Schouten and Van den Bleek 1998 showed that it is not: the agglomeration of plastic particles in a laboratory-scale fluidized bed at elevated temperature was not detected by monitoring the average pressure drop until defluidization has occurred. In that case it is often too late; a functional monitoring method should give an early warning such that defluidization can be pre®ented.…”
Section: Pressure Dropmentioning
confidence: 94%
“…hydrodynamics. Schouten and Van den Bleek 1998 showed that it is not: the agglomeration of plastic particles in a laboratory-scale fluidized bed at elevated temperature was not detected by monitoring the average pressure drop until defluidization has occurred. In that case it is often too late; a functional monitoring method should give an early warning such that defluidization can be pre®ented.…”
Section: Pressure Dropmentioning
confidence: 94%
“…This will benefit several different areas of work associated with fluidized beds, including issues related to hydrodynamic and heat-transfer similitude, 1,2 chemical processes occurring in fluidized beds, 3,4 and the use of pressure fluctuations as a diagnostic tool for the fluidized bed's performance and fluidization regime identification. [5][6][7][8] The testing and analysis methods used to evaluate fluidized-bed pressure fluctuations have varied widely among researchers. Brue and Brown investigated sampling and analysis techniques traditionally used to measure and interpret pressure fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…18 Pressure fluctuations can also be employed to characterize the quality of fluidization or the performance of a fluidized bed. [19][20][21][22][23] For example, low amplitudes and higher frequencies of the pressure fluctuations tend to manifest the occurrence of small gas pockets (bubbles) or small particle clusters that can lead to intensive heat and mass transfer in the bed.…”
Section: Introductionmentioning
confidence: 99%